PROGRAM PENINGKATAN KETERAMPILAN BELAJAR (STUDY SKILLS) UNTUK MAHASISWA BARU - Nani Nuranisah Djamal (Psympathic : Jurnal Ilmiah Psikologi, 2008)
The research will be conducted based on the fact that most of students are lack of capability to study at higher education. It is proved by the unsatisfied result of their first year study (the students of academic-year 2003, 2004 and 2005). Most of them are realize that they are incapable to study the subjects of their major.